Satire Pada Puisi “Sajak Seonggok Jagung” Karya W. S. Rendra: Kajian Stilistika - Lolita, Asri (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study aims to analyze stylistics in revealing satire in the poem